2013
DOI: 10.6026/97320630009238
|View full text |Cite
|
Sign up to set email alerts
|

Production of extracellular enzymes in the entomopathogenic fungus Verticillium lecanii

Abstract: This study investigates the mechanisms as well as strategies for purification and characterization of potential enzymes involved in pathogenesis of entomopathogenic fungi. The test strain of Verticillium lecanii that was screened, during the present investigation, proved to be an efficient producer of protein and polysaccharide degrading enzymes (amylase, protease, and lipase), hence indicating versatility in biochemical mechanisms. Halo zones produced colony growth of V. lecanii on agar confirmed activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 14 publications
0
21
1
Order By: Relevance
“…Proteinases were secreted by fungi growing in the media with both the maximal and minimal nitrogen content (Table 1), which suggests that their synthesis was constitutive. Pronounced activity of proteolytic enzymes in ento mopathogenic and carnivorous micromycetes may be associated with their involvement in the pathogenic processes in invertebrates [20,21]. It should be noted that zygomycetes were less active towards the protein substrates utilized than asco mycetes.…”
Section: Resultsmentioning
confidence: 99%
“…Proteinases were secreted by fungi growing in the media with both the maximal and minimal nitrogen content (Table 1), which suggests that their synthesis was constitutive. Pronounced activity of proteolytic enzymes in ento mopathogenic and carnivorous micromycetes may be associated with their involvement in the pathogenic processes in invertebrates [20,21]. It should be noted that zygomycetes were less active towards the protein substrates utilized than asco mycetes.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 6, V. lecanii colonization in the abdomen and the insect's body appear as a mass of mycelium with a few spores with cleavage of the cuticle and the presence of the fungal growth inside the body. The strain of V. lecanii was screened in a study (Hasan et al, 2013) and proved to be an efficient producer of protein and polysaccharide degrading enzymes (amylase, protease, and lipase). It was found to be an outstanding source of enzyme secretion and can be rationally utilized towards the production of improved mycopesticides.…”
Section: Resultsmentioning
confidence: 99%
“…However, Ali et al (2011) reported that the optimum extracellular protease activity of M. anisopliae was at pH 8. On the other hand, Hasan et al (2013) revealed that the highest proteolytic activity of the Verticillium lecanii was at pH 7-9.…”
Section: Effect Of Phmentioning
confidence: 96%